2022
DOI: 10.3390/cancers14092291
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia as a Modulator of Inflammation and Immune Response in Cancer

Abstract: A clear association between hypoxia and cancer has heretofore been established; however, it has not been completely developed. In this sense, the understanding of the tumoral microenvironment is critical to dissect the complexity of cancer, including the reduction in oxygen distribution inside the tumoral mass, defined as tumoral hypoxia. Moreover, hypoxia not only influences the tumoral cells but also the surrounding cells, including those related to the inflammatory processes. In this review, we analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 320 publications
0
12
0
Order By: Relevance
“…It is significant to clarify the mechanism responsible for the synergistic effects of IL-6 and hypoxia on EMT. Signal transducer and activator of transcription proteins (STATs) has been identified as an essential mediator of the inflammation and hypoxia [ 40 ]. STATs will be activated after binding to their receptors of certain growth factors or cytokines, such as IL-6 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is significant to clarify the mechanism responsible for the synergistic effects of IL-6 and hypoxia on EMT. Signal transducer and activator of transcription proteins (STATs) has been identified as an essential mediator of the inflammation and hypoxia [ 40 ]. STATs will be activated after binding to their receptors of certain growth factors or cytokines, such as IL-6 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Purine nucleotide metabolism targets MICA, A1, A2A, A2B, and A3 and relates to NK, Monocytes, Macrophages, and Dendritic and T immune cells. 60 Genes with substrates and applied therapeutics in disease eradication are present. Further studies are needed to understand the purine nucleotide metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Such an unfavorable condition may further facilitate the ORN development by leading to the emergence of difficult to manage infections, exacerbated inflammation, and subsequent impairment of tissue repair, as most immune cells demand adequate oxygen levels to operate effectively [ 41 ]. Hypoxia induced secretion of HIF-1α and associated cytokines can generate and/or worsen systemic and localized inflammation, which can further deepen the hypoxic state and establish a vicious cycle of inflammation and hypoxia [ 34 36 ]. Given that low hemoglobin levels represent a state of systemic and localized hypoxia, all of these basic mechanisms, along with exacerbated hypoxia created by low hemoglobin levels, appear to support Marx’s theory of radiation-induced vasculature impairment, hypoxia, and impaired wound repair as the primary causes of ORN pathogenesis, though secondary infections may also play a role [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, platelets produce vascular occlusion by participating in primary hemostasis, hence it has been suggested that a high platelet count may promote hypoxia by interrupting blood flow at the tissue and vessel levels [ 33 ]. Stimulated hypoxia-induced factor-1 (HIF-1) and angiogenic factors such as vascular endothelial growth factor (VEGF), transforming growth factor (TGF-α and TGF-β) have been shown to play critical roles in the ORN development due to reduced vascularization and tissue hypoxia [ 34 36 ].…”
Section: Introductionmentioning
confidence: 99%